Faktor-Faktor yang Memengaruhi Status Setengah Penganggur di Sulawesi Barat Tahun 2022 - Achmad, Farchany; Rahani, Rini (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
Underemployment is a condition of employment where workers work less than 35 hours and are still looking for work or willing to accept work. The Underemployment Rate in West Sulawesi was the second highest with the most significant increase compared to other provinces. This study aimed to describe the overview of Underemployment Status, the effect of individual and regional variables and their tendencies on Underemployment Status in West Sulawesi Province using Sakernas raw data in August 2022, welfare statistics and Sulawesi Barat Province in Figure 2023. The statistical method used was multilevel binary logistic regression analysis with random intercept. The results showed that Male workers, aged 15-24 years, having partner status, having at least high school or equivalent education, working in the informal sector, working in the agricultural field, being head of household, and living in rural areas had higher tendencies of being underemployed. The decline of job availability in West Sulawesi caused highly educated workers to be more likely to be underemployed than those with lower levels. At the regional level, only the UMK did not influence unemployment status. Meanwhile, the low morbidity rate was statistically significant in decreasing the underemployment rate in West Sulawesi.